Crop-livestock integration and technology choices for improving fodder availability, livestock productivity and famers’ income in West Africa - Kumar, Shalander; Pramanik, Soumitra; Umutoni, Clarisse; Rich, Karl M.; Bado, Vincent; Whitbread, Anthony (International Crops Research Institute for the Semi-Arid Tropics, 2021)
The present study generates evidence to better understand the interactions and tradeoffs between crops and livestock enterprises in a whole-farm systems context in West Africa. Hardly any literature is available on the effect of different crop-livestock integration and technology choices on the livestock value chains in a whole-farm way in the region. This study uses diverse primary and secondary sources of data, such as focussed group discussions with different crop-livestock value chain actors, published literature and personal interviews with 390 farm households in Niger and Burkina Faso. We developed scenarios applying model-based, whole-farm crop-livestock method to illustrate possible benefits and impacts of integrating dual-purpose crops and cultivars on farm productivity and income, and availability of animal-sourced food. Whole-farm scenarios developed with assistance from stakeholders and experts consultations were used to measure and illustrate possible impacts, testing different technical (livestock breeds, health intervention), and institutional innovations (markets, policies). Finally, the analysis helped in identifying strategies for integrating suitable dual-purpose crops and cultivars, and type of livestock to improve livestock productivity, marketability, and income for improving rural livelihoods, and increasing availability of animal-sourced food in Niger and Burkina Faso.